Effects of earthquakes and other natural catastrophic events on the sex ratio of newborn infants. (January 2020) - Fukuda, Misao; Fukuda, Kiyomi; Mason, Shawn; Shimizu, Takashi; Andersen, Claus Yding
Abstract: Stress due to earthquakes and other natural catastrophic events may result in a decline in the male to female ratio of newborn infants. One reason may be an increased death of male fetuses 3–5 months earlier. Another reason may relate to reduced conception of males and/or early male embryo demise 8–10 months earlier. Almost all of the earthquakes and natural catastrophic events have caused declines in sex ratios at birth except the Hurricane Katrina which showed a rise in the birth sex ratio. We describe hypothetical immunological cause for the decline in the sex ratio at birth following periods of augmented stress levels.